2019
DOI: 10.1007/s11483-019-09574-2
|View full text |Cite
|
Sign up to set email alerts
|

Submaxillary Mucin: its Effect on Aroma Release from Acidic Drinks and New Insight into the Effect of Aroma Compounds on its Macromolecular Integrity

Abstract: Submaxillary mucin is a major component that defines the makeup and functionality of saliva. Understanding its structure and function during food intake is key to designing appropriate strategies for enhancing the delivery of flavour. In the present study, the hydrodynamic integrity of bovine submaxillary mucin was characterised under physiological and acidic conditions and it was shown to have a broad molecular weight distribution with species ranging from 100 kDa to over 2000 kDa, and a random coil type of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…The sedimentation velocity results show the distribution of sedimentation coefficients for 1.0 mg/mL BSM solution, revealing a broad polydisperse distribution ranging from 2 to 12S, as shown previously (Dinu et al 2019a ). The addition of linear aldehydes and ketone volatile compounds was shown to result in an increase in the proportion of species of high sedimentation rates, tailing up to ~ 28S for the mixtures containing more hydrophilic compounds such as butanone or hexanal (Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The sedimentation velocity results show the distribution of sedimentation coefficients for 1.0 mg/mL BSM solution, revealing a broad polydisperse distribution ranging from 2 to 12S, as shown previously (Dinu et al 2019a ). The addition of linear aldehydes and ketone volatile compounds was shown to result in an increase in the proportion of species of high sedimentation rates, tailing up to ~ 28S for the mixtures containing more hydrophilic compounds such as butanone or hexanal (Fig.…”
Section: Resultssupporting
confidence: 86%
“…The elution profiles (Fig. 2 ) reveal a broad multi-component distribution of BSM, ranging from ~ 16 to 24 min, as reported previously (Dinu et al 2019a ). However, the addition of hexanal led to the formation of larger moieties (Peak 2), which appear to be up to ten times larger than the average molecular mass for Peak 1.…”
Section: Resultssupporting
confidence: 85%
“…Previous research by Castro and Ross 7 has shown that the non-volatile matrix affects the headspace partitioning, as well as the sensory perception of volatile compounds in a model beer due to a physical suppression effect. Other research has also shown that an increased proportion of macromolecules in solution affects the rate of diffusion of aroma compounds, thereby leading to a lower aroma release [41][42][43][44] .…”
Section: Discussionmentioning
confidence: 99%
“…They have the formidable ability to act as a permeability barrier, regulating access across to the epithelium. Most mucins are heavily glycosylated, although they do contain regions of unglycosylated polypeptide, predominantly composed of cysteine, serine, threonine and proline 93 . Serine, threonine and proline assist in the coiling of the glycoprotein, which may give rise to potential protein-aroma interaction sites through hydrogen bonding and hydrophobic interactions.…”
Section: Interactions Of Flavour Compounds With Biological Structuresmentioning
confidence: 99%
“…Interactions with phenolic aroma compounds have also been documented. For instance, p-cresol, a by-product of citral degradation, which is present in some citrus-flavoured drinks, was shown to interact with mucins to result in the formation of smaller fragments 93 . A similar compound is m-cresol that has long been used as an excipient in insulin formulations in order to deaggregate insulins and keep the proteins in their active, monomeric form 98 .…”
Section: Interactions Of Flavour Compounds With Biological Structuresmentioning
confidence: 99%